Satisfacción laboral y desempeño de los trabajadores de la Financiera Compartamos de la ciudad de Iquitos, año 2022 - Piña Tapullima, Lorena Naoko (2025)
Our study carried out at Financiera Compartamos in the city of Iquitos aimed to determine the relationship between job satisfaction and worker performance using a quantitative research approach. The most notable result of the study was a (two-sided) sigma value of 0.000, indicating a very high degree of significance. According to the established decision rule, when the calculated sigma value is less than 0.05, the alternative hypothesis (Ha) is accepted. The data collected in the survey is presented in Table 03, and reveals that the Pearson correlation coefficient between job satisfaction and worker performance is equal to 0.953. This value indicates a positive and highly significant correlation between Variable 1 (job satisfaction) and Variable 2 (worker performance), the findings of the study conclusively validate that there is a significant relationship between job satisfaction and employee performance. workers at Financiera Compartamos in the city of Iquitos in the year 2022, supported by the extremely low sigma value and the high Pearson correlation obtained in the research.